Lower rates of return to sport in patients with generalised joint hypermobility two years after ACL reconstruction: a prospective cohort study - Jakob Lindskog; Ramana Piussi; Rebecca Simonson; Johan Högberg; Kristian Samuelsson; Roland Thomeé; David Sundemo; Eric Hamrin Senorski (BMC, 2023)
Abstract Background Generalised joint hypermobility (GJH) has been associated with an increased risk of suffering an anterior cruciate ligament (ACL) injury. Patients with GJH exhibit lower muscle strength and poorer scores for patient-reported outcomes after ACL reconstruction, compared with patients without GJH. The aim of this study was to examine differences in the percentages of patients who return to sport (RTS) or pre-injury level of activity (RTP), muscle function and patient-reported outcomes at the time of RTS or RTP, as well as the time of RTS or RTP in patients with GJH compared with patients without GJH in the first two years after ACL reconstruction. Methods This prospective study used data from an ACL- and rehabilitation-specific register located in Gothenburg, Sweden. Patients aged between 16 and 50, who had a primary ACL injury treated with reconstruction, were included. Data up to two years after ACL reconstruction were used and consisted of achieving RTS and RTP, results from isokinetic muscle function tests for knee extension and flexion and patient-reported outcomes (Knee Self-Efficacy Scale, Knee injury and Osteoarthritis Outcome Score and ACL-Return to Sport after Injury scale) at the time of RTS, as well as the time of RTP. A Beighton Score of ≥ 5/9 was used to define GJH. A Tegner Activity Scale of ≥ 6 was used to define RTS, while a Tegner equal to or above pre-injury level was used to define RTP. Results A total of 1,198 patients (54.7% women) with a mean age of 28.5 ± 8.6 years were included. A smaller proportion of patients with GJH achieved RTS compared with patients without GJH (49.2% vs. 57.3%, Odds ratio: 0.720, p = 0.041). Furthermore, patients with GJH were marginally less symmetrical on the knee extension strength test, expressed as a Limb Symmetry Index, at the time of RTP compared with patients without GJH (87.3 ± 13.5 vs. 91.7 ± 14.3, Cohen's d = 0.142, p = 0.022). No further differences were found between groups regarding any muscle function tests or patient-reported outcomes. Conclusion A smaller proportion of patients with GJH achieved RTS compared with patients without GJH. Patients with GJH displayed less symmetrical knee extension strength at the time of RTP compared with patients without GJH.